The Centenary of Immune Thrombocytopenia—Part 2: Revising Diagnostic and Therapeutic Approach - Consolini, Rita; Costagliola, Giorgio; Spatafora, Davide (Frontiers in Pediatrics, 2017)
Immune thrombocytopenia is the most common cause of thrombocytopenia in children and adolescents, and can be considered as a paradigmatic model of autoimmune disease. This second part of our review describes clinical presentation of ITP, the diagnostic approach and overviews the current therapeutic strategies. Interestingly, it suggests an algorithm useful for differential diagnosis, a crucial process to exclude secondary forms of immune thrombocytopenia and non-immune thrombocytopenia, which require a different therapeutic management. Advances in pathogenesis led to new therapeutic targets, as Thrombopoietin (TPO) and their receptors, whose role in treatment of IT will be discussed in this work.